Who is Responsible for Corruption? Framing strategies of social movements in West Africa mobilizing against presidential term amendments - Prause, Louisa; Wienkoop, Nina-Kathrin (PARTECIPAZIONE E CONFLITTO, 2018)
Since 2011 youth movements have staged large protests in African countries for presidential term limits. These have been discussed as struggles against de-democratization. Looking at the movements Y’en a marre in Senegal and Balai citoyen in Burkina Faso we argue that these protests were just as much triggered by socio-economic grievances linked to a corrupt patronage system. Indeed, corruption has been a major issue for both campaigns. We ask how the movement leaders linked the fight against corruption with their struggle against third term amendments in a way that sparked mass mobilization. We use the framing approach as our theoretical framework and show that a framing based on the concept of citizenship enabled both movements to link the issue of corruption to the issue of presidential term amendments and at the same time create a sense of agency in the constituency. This explains at least partly why both Y’en a marre and Balai Citoyen succeeded in their mobilizing efforts.